2006
DOI: 10.1080/10683160500350546
|View full text |Cite
|
Sign up to set email alerts
|

Theory and practice in interviewing young children: A study of Norwegian police interviews 1985–2002

Abstract: Has the increased public and professional awareness of the challenges of interviewing children in forensic contexts led to changes and improvements in police interviewing practices? A representative sample (n0/91) of police interviews conducted during the period of 1985 Á2002 from a large Norwegian police district was analysed. The results indicated that interviewer strategies have improved; there was a decrease in the use of suggestive, yes/no and option-posing questions and this decrease was accompanied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 26 publications
5
30
0
Order By: Relevance
“…Overall, more than 80% of the questions asked by interviewers were focused, and only 6% were open-ended and allowed free recall of the abuse. These results have been consistently replicated in several countries, including Australia, Canada, Finland, Great Britain, Israel, Norway, Sweden, and the United States (Aldridge & Cameron, 1999;Cederborg, Orbach, Sternberg, & Lamb, 2000;Cyr & Lamb, 2009;Faller, 1996;Korkman, Santtila, Westeraker, & Sandnabba, 2008;Lamb et al, 2009;Orbach et al, 2000;Myklebust & Bjorklund, 2010;Sternberg, Lamb, Davies, & Westcott, 2001;Thoresen, Kyrre, Melinder, Stridbeck, & Magnussen, 2006). Although a recent study (Thoresen, Lonnum, Melinder, & Magnussen, 2009) has observed some changes in the quality of Norwegian forensic interviews over a period of 10 years (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), including a decrease in leading questions, the number of open-ended questions remained low throughout the interview, suggesting that interviewers continued to rely, to a large extent, on closed questioning.…”
supporting
confidence: 49%
“…Overall, more than 80% of the questions asked by interviewers were focused, and only 6% were open-ended and allowed free recall of the abuse. These results have been consistently replicated in several countries, including Australia, Canada, Finland, Great Britain, Israel, Norway, Sweden, and the United States (Aldridge & Cameron, 1999;Cederborg, Orbach, Sternberg, & Lamb, 2000;Cyr & Lamb, 2009;Faller, 1996;Korkman, Santtila, Westeraker, & Sandnabba, 2008;Lamb et al, 2009;Orbach et al, 2000;Myklebust & Bjorklund, 2010;Sternberg, Lamb, Davies, & Westcott, 2001;Thoresen, Kyrre, Melinder, Stridbeck, & Magnussen, 2006). Although a recent study (Thoresen, Lonnum, Melinder, & Magnussen, 2009) has observed some changes in the quality of Norwegian forensic interviews over a period of 10 years (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), including a decrease in leading questions, the number of open-ended questions remained low throughout the interview, suggesting that interviewers continued to rely, to a large extent, on closed questioning.…”
supporting
confidence: 49%
“…Similar findings were made in other Nordic countries (e.g. Cederborg et al 2000; Thoresen et al 2006;Thoresen et al 2009), showing that investigative interviews were often of poor quality.…”
Section: The Legal and Theoretical Framework For Assessing Allegationsupporting
confidence: 69%
“…Furthermore, all Protocol interviews were necessarily conducted after the comparison interviews (interviewers cannot be untrained) making it possible that effects were simply attributable to practice. This interpretation is implausible, however, in light of multiple studies, conducted in a number of jurisdictions, including the UK, showing that, regardless of length of experience, forensic interviewers never use as many open-ended prompts on average as the interviewers in the Protocol condition did (Cederborg et al, 2000;Craig et al, 1999;Cyr & Lamb, 2007;Davies et al, 2000;Korkman et al, 2006;Lamb, Hershkowitz, Sternberg, Boat, et al, 1996;Lamb, Hershkowitz, Sternberg, Esplin, et al, 1996;Sternberg, Lamb, Orbach, et al, 2001;Thoresen et al, 2006;Walker & Hunt, 1998;Warren et al, 1996).…”
Section: Discussionmentioning
confidence: 97%